Social franchising of community‐based HIV testing and linkage to HIV care and treatment services: an evaluation of a pilot study in Tshwane, South Africa. Issue 12 (20th December 2018) - Shamu, Simukai; Farirai, Thato; Kuwanda, Locadiah; Slabbert, Jean; Guloba, Geoffrey; Johnson, Suzanne; Khupakonke, Sikhulile; Masihleho, Nomea; Kamera, Julius; Nkhwashu, Nkhensani
Abstract: Introduction: Although HIV testing services (HTS) have been successfully task‐shifted to lay counsellors, no model has tested the franchising of HTS to lay counsellors as independent small‐scale business owners. This paper evaluates the effectiveness of a social franchisee (SF) HTS‐managed pilot project compared to the Foundation for Professional Development (FPD) employee‐managed HTS programme in testing and linking clients to care. Methods: Unemployed, formally employed or own business individuals were engaged as franchisees, trained and supported to deliver HTS services under a common brand in high HIV‐prevalent communities in Tshwane district between 2016 and 2017. SFs were remunerated per‐HIV test and received larger payments per‐HIV‐positive client linked to care. In the standard HTS, FPD employed counsellors received similar training and observed similar standards as in the SF HTS, but were remunerated through the normal payroll. We assessed the proportion of clients tested, HIV positivity, linkage to care and per‐counsellor cost of HIV test and linkage to care in the two HTS groups. Results: The SF HTS had 19 HIV counsellors while FPD HTS employed 20. A combined total of 84, 556 clients were tested by SFs (50.5%: 95% confidence interval (CI) 50.2 to 50.8)) and FPD (49.5%: 49.2 to 49.8). SFs tested more females than FPD (54.1%: 53.6 to 54.6 vs. 48%: 47.7 to 48.7). SFs identified more first‐time testers than FPD (21.5%: 21.1 to 21.9 vs. 8.9%: 8.6 to 9.1). Overall, 8%: 7.9 to 8.2 tested positive with more clients testing positive in the SF (10.2%: 9.9 to 10.5) than FPD (5.9%: 5.6 to 6.1) group. The SFs identified more female HIV‐positive clients (11.1%: 10.7 to 11.6) than FPD (6.5%: 6.2 to 6.9). The SFs linked fewer clients to HIV care and treatment (60.0%: 58.5 to 61.5) than FPD (80.3%: 78.7 to 81.9%). It cost four times less to conduct an HIV test using SFs ($3.90 per SF HIV test) than FPD ($13.98) and five times less to link a client to care with SFs ($62.74) than FPD ($303.13). Conclusions: SF HTS was effective in identifying more clients, first‐time HIV testers and more HIV‐positive people, but less effective in linking clients to care than FPD HTS. The SF HTS model was cheaper than the FPD‐employee model. We recommend strengthening SFs particularly their linkage to care activities.